Enhancing Students' Emotional Intelligence through Project-Based Math Education - Sahara, Rifki (LP. Ma'arif Janggan Magetan, 2024)
The increasing challenges faced by students in learning mathematics, particularly in managing academic anxiety and emotional stress, highlight the need for innovative teaching methods that not only focus on cognitive skills but also foster emotional intelligence. This study aims to investigate the role of Project-Based Learning (PBL) in enhancing students' emotional intelligence, specifically within the context of mathematics education. The research employs a literature review approach, synthesizing findings from various studies to explore how PBL influences emotional and social development alongside academic performance. The findings reveal that PBL significantly improves students' self-awareness, emotional regulation, and social skills by fostering a collaborative learning environment where real-world problems are solved in teams. However, the study also identifies challenges in PBL implementation, such as the complexity of project design and insufficient teacher training in integrating emotional intelligence into mathematics learning. Addressing these challenges through targeted teacher training is essential to fully realize the potential of PBL. The conclusion emphasizes that PBL not only enhances cognitive and emotional development but also promotes educational equity by narrowing academic achievement gaps among students from diverse socio-economic backgrounds.